THE EFFECT OF DIFFERENT SHADE LEVELS ON THE GROWTH AND YIELD OF Asystasia gangetica (L.) subsp. Micrantha ON THE SECOND CUT - K., Gunawan; Witariadi, N. M.; Kusumawati, N. N. C. (Jurnal Peternakan Tropika; Vol 12 No 1 (2024): Vol. 12 No. 1 Tahun 2024; January - February, 2024)
This study aims at investigating the effect of different shade levels on the growth and yield of Asystasia gangetica (L.) subsp. Micrantha on the second cutting. The research was conducted in the greenhouse of Sading Village, Mengwi District, Badung Regency and the research was conducted from May-July 2022.  The design used was a completely randomized design (CRD) consisting of four treatments, each repeated seven times, resulting in 28 experimental units. The treatments were: N0: 0% shade (without shade net); N1: 20% shade (1 layer of shade net); N2: 40% shade (2 layers of shade net); and N3: 60% shade (3 layers of shade net). The observed variables were growth variables, yield variables, and plant growth characteristics. The results showed that shade levels had an effect on growth, yield, and plant growth characteristics. Therefore, it was concluded that shade levels had an effect on the growth and yield of Asystasia gangetica in the second cutting. The 20% and 40% shade level (N1 and N2) provided the best growth and yield for Asystasia gangetica (L.) subsp. Micrantha in the second cutting.